Creative Economy: Reviewing Global Political Narratives - Demeiati Nur Kusumaningrum (Journal of Islamic World and Politics, 2024)
Indonesia, as the biggest Muslim country in 2019, promoted the creative economy as a crucial entity for achieving sustainable development, as adopted in UN Resolution No. 74/198. It demonstrates the acceptance of the creative economy as an international approach to the development strategy post-pandemic COVID-19. Considering the restructuring sustainable development framework that internalized the current issue of creative economy, this paper aims to discuss the conceptualization of creative economy as a global discourse. It used a narrative literature review by combining a bibliographic analysis process in order to explore a consistent, comprehensive, and in-depth understanding of existing knowledge on the subject of the creative economy. Data sources obtained from the internet consist of Scopus and Google Scholar journal articles. The official government and international organization websites are also used to confirm the research arguments. The study examines the conceptualization of creative economy, which refers to cultural economy, cultural industry, creative industry, and cultural policy. The diffusion of ideas played by multi-actors in a networked process led to the acceptance of the creative economy as a global discourse. The United Nations has a platform role in institutionalizing the ideas and beliefs about the creative economy as a significant entity for the global development agenda.